Detached Eddy Simulations of a Reaction Control Jet from an Axi-Symmetric Body in a Supersonic Crossflow (MIST International Journal of Science and Technology, 2024)
The introduction of a control jet into a supersonic cross flow yields a substantial region of separated flow, manifesting in the vicinity of the injection site. This, in turn, alters the distribution of pressure on the primary body, thereby influencing the effectiveness of the injected jet’s capacity to produce the desired control forces and moments. In the context of an axi-symmetric parent body, this disruption typically leads to a reduction in effectiveness, owing to the overflow of the shock structures encompassing the parent body. The present study investigates the injection of a reaction control jet into a supersonic crossflow using different Detached Eddy Simulation (DES) techniques. The side jet is injected from an orifice on an axi-symmetric parent body, which is aligned with the crossflow direction. The effects of the side jet on the flow field are analysed in terms of general flow features and spectral behaviour of pressure and turbulent kinetic energy. The DES results are compared with those obtained from RANS using various turbulence models. The overall effect of a transient interaction pulse is characterized using URANS and two different DES models.MIJST, Vol. 12, June 2024 : 01-09DOI: https://doi.org/10.47981/j.mijst.12(01)2024.459(01-09)